Vocational education and training in Estonia : short description - (:unkn) unknown (Publications Office of the European Union, 2017)
"Estonian VET has been changing over the past decade, reflecting both demographic trends and the changing needs of the labour market. The VET school network has been optimised to raise its efficiency, with small providers merged into bigger regional centres offering a wide range of qualifications. Participation in lifelong learning has increased, VET having an important role in this process. The share of adults in VET has more than doubled since 2010/11 and reached about a third of the total VET population. Apprenticeships have also been expanding: while their share is still relatively low, the number of apprentices has doubled in the past year. These and other changes are supported by reforms that aim at making VET a more attractive option for learners." (editor; BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; S 1.3 Berufliche Erstausbildung; S 1.5.2 Berufliche Weiterbildung; I 2.2.2 Osteuropa; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Estland